Upstream migration capacity of Acrossocheilus fasciatus: Behavioral strategies in response to hydraulic conditions and implications for low-head weir design - Bin Wang; Gang Xu; Lei Fu; Aiju You; Zeqi Xu; Yue Ling (PLoS ONE, 2026)
Current fishway design guidelines are mostly derived from large anadromous fish species, with scarce species-specific data for small-bodied stream cyprinids such as Acrossocheilus fasciatus . This study investigated the upstream passage capacity of the cyprinid fish A. fasciatus over low-head weirs in relation to body length through controlled flume experiments. We quantified the passage success rate (PSR), behavioral strategies, and key kinematic metrics of upstream movement. Results showed that, under the specific experimental conditions, passage performance and strategy usage pattern were significantly associated with body length. Trial groups with larger mean body length showed a higher proportion of pure leaping strategy (PLS), mean body length per trial group exhibited an extremely strong positive linear relationship with mean leap distance ( R ² = 0.96, p < 0.001). Conversely, groups with smaller mean body length showed a higher proportion of Leaping-Swimming Strategy (LSS) usage. The association between body length and leap height was weaker. Under the specific hydraulic and structural conditions tested in this study, we observed the following trends: a weir drop of 25–30 cm allowed partial passage of A. fasciatus ; the fixed 45° sloped crest profile used in this experiment was associated with prevalent adoption of the LSS by small-bodied individuals (≤13 cm); a downstream pool depth >30 cm and an inter-weir pool length >50 cm were sufficient to accommodate the observed leaping kinematics. These findings provide observational data from a single laboratory configuration for understanding the passage-related bio-behavioral characteristics of small-bodied mountain stream fishes such as A. fasciatus . All values reported are preliminary observations under controlled conditions, and their potential relevance to engineering design requires validation through multi-condition comparative experiments and field monitoring.